Analisis Kandungan Timbal (Pb) pada Daun Glodokan Tiang (Polyalthia longifolia) di Kecamatan Medan Johor, Medan - Lutfi Wahyu Ananda; Abdul Hakim Daulae (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
High traffic density in urban areas triggers an increase in heavy metal lead (Pb) emissions in the air. This pollution can be assessed using shade plants as bioindicators, such as the mast tree (Polyalthia longifolia). This study used a descriptive quantitative approach aimed at determining the heavy metal lead (Pb) content and its relationship with traffic density in the Medan Johor District. Sampling was conducted at three locations with different traffic densities (AH. Nasution Street, Karya Amal Street, and Eka Suka Street) using a purposive sampling method, with a total of 9 leaf samples from the three observation stations. Leaf samples were analyzed in the laboratory using an Atomic Absorption Spectrophotometer (AAS). The results showed that the highest Pb content was found in the location with high traffic density (AH. Nasution Street) at 0.0668 mg/kg, while in locations with medium and low densities, the values were below the detection limit (<0.0017 mg/kg). Pearson correlation analysis indicated a very strong and significant relationship (r = 0.941, p < 0.05) between the number of vehicles and lead content. This means that the higher the traffic density, the higher the Pb accumulation in the leaves. It can be concluded that traffic density significantly affects lead accumulation in mast tree leaves, thus this plant has the potential to be used as an air pollution bioindicator in urban areas.